2022
DOI: 10.1155/2022/9075263
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Exchange Rate Pass‐Through to Consumer Prices in Ghana: Evidence from EMD‐NARDL Approach

Abstract: This paper analyses the US dollar exchange rate pass-through to consumer prices in Ghana from January 1990 to January 2020 using the empirical mode decomposition-based nonlinear autoregressive distributed lags model (EMD-NARDL). This model eliminates the noise component of the underlying data and captures the short- and long-run nonlinearities. We find evidence of cointegration between denoised series of consumer prices and exchange rate and asymmetric pass-through in both the short- and long-run. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Accordingly, the stock returns and interest rate nexus could be bi-directional across time. However, it is expected that in the context of a developing economy, a negative nexus is more practicable due to growth constraints in times of poorly performing macroeconomic indicators (Owusu-Ankamah and Sakyi 2021; Amegavi et al 2022;Obeng et al 2022). Hence, the following research hypothesis is found:…”
Section: Nexus Between the Indicators Of The Gse And Interest Rate Me...mentioning
confidence: 97%
“…Accordingly, the stock returns and interest rate nexus could be bi-directional across time. However, it is expected that in the context of a developing economy, a negative nexus is more practicable due to growth constraints in times of poorly performing macroeconomic indicators (Owusu-Ankamah and Sakyi 2021; Amegavi et al 2022;Obeng et al 2022). Hence, the following research hypothesis is found:…”
Section: Nexus Between the Indicators Of The Gse And Interest Rate Me...mentioning
confidence: 97%
“…The study also concluded that although the relationship between price level and exchange rate is not unidirectional, the short run effect of devaluation on prices is smaller than the effect of inflation on exchange rate. (Obeng, 2022) study focused on the asymmetric nature of the impact of exchange rate on inflation using NARDL. Using Ghana monthly economic data from January 1990 to January 2020, the study found that the cointegration between inflation rate and exchange rate in Ghana is asymmetric in both short and long run.…”
Section: The Asymmetric Impact Of Exchange Rateon Inflation In Egypt ...mentioning
confidence: 99%
“…Camara et al. (2022) analyzed the US dollar ERPT to consumer prices in Ghana from January 1990 to January 2020 using a non-linear ARDL model.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Stronger ERPT is associated with countries that have a higher dollarization and current account deficit, as well as higher inflation, a higher risk premium and higher foreign currency (FX) debt levels. Camara et al (2022) analyzed the US dollar ERPT to consumer prices in Ghana from January 1990 to January 2020 using a non-linear ARDL model. Accordingly, they have proved the existence of cointegration between the exchange rate and consumer prices.…”
Section: Empirical Reviewmentioning
confidence: 99%